Nutritional rehabilitation for children with cystic fibrosis: Single center study. (February 2020) - El-Koofy, Nehal; El-Mahdy, Mai; Fathy, Mona; El Falaki, Mona; El Dine Hamed, Dina Hossam
Summary: Background: Cystic fibrosis (CF) is an inherited disorder that causes severe damage to multiple organs in the body. Nutritional management has a dramatic effect on growth and survival in CF patients. This study aimed to assess the nutritional status of Egyptian pediatric patients with CF before and after proper nutritional counseling and supplementation. Methods: This is an interventional observational study conducted on fifty children with CF recruited from CF clinic, Children's Hospital, Cairo University. The patients were subjected to history taking, clinical examination, full nutritional assessment, including signs of vitamins deficiencies, Subjective global assessment (SGA), anthropometric measurements, laboratory assessment (complete blood count, kidney, liver function tests and Prealbumin as a nutritional marker). After the initial assessment all the patients were subjected to a proper nutritional plan plus vitamin and mineral supplementations then reassessed them after 3 months. Results: SGA showed that 60% of the patients had severe malnutrition, 62%, 78%, and 48% of the patients were below −2 Z score for height, weight, and BMI respectively which decreased to 45%, 40%, and 32% after nutritional supplementation. 43% of the patients were anemic, 29% were hypoalbuminemic, and 80% had low serum Prealbumin levels. After 3 months of follow up, only 17% had anemia, 11% had hypoalbuminemia, and 41% had low serum Prealbumin. Compliance was detected in 76% of caregivers during the follow up. Conclusion: CF patients had considerable impairment in their nutritional status. Proper caloric intake and vitamin supplementation had a valuable impact on their growth and prognosis.